2006
DOI: 10.1177/07419325060270030201
|View full text |Cite
|
Sign up to set email alerts
|

The Teacher Support Program

Abstract: Several challenges characterize the special education profession. The literature is replete with reports of high levels of stress, burnout, and attrition among special educators; the lack of a sufficient number of fully qualified teachers; and dissatisfaction with the gap that exists between research-based effective practices and the daily classroom practices of teachers. In an attempt to counter these conditions, a model Teacher Support Program was developed in western North Carolina that offered several supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Multiple and varied academic needs are often the greatest challenge for teachers implementing inclusive practices who are concerned not only about student performance, but their own accountability and teaching evaluations as well [37,38]. Räty et al [33] found that strategies such as the use of graphic organizers, visual supports, direct instruction, time delay (increased wait time with cues and prompts), and making real-life connections are EBPs that support instruction across all disciplines.…”
Section: Challenges Of Including Individuals With Intellectual Disabi...mentioning
confidence: 99%
“…Multiple and varied academic needs are often the greatest challenge for teachers implementing inclusive practices who are concerned not only about student performance, but their own accountability and teaching evaluations as well [37,38]. Räty et al [33] found that strategies such as the use of graphic organizers, visual supports, direct instruction, time delay (increased wait time with cues and prompts), and making real-life connections are EBPs that support instruction across all disciplines.…”
Section: Challenges Of Including Individuals With Intellectual Disabi...mentioning
confidence: 99%
“…Teachers of older students also report higher levels of burnout (Carlson & Thompson, 1995; Frank & McKenzie, 1993). However, other authors argue that teachers’ perceptions and responses to student issues (i.e., diversity of student needs, lack of student progress; discipline problems) rather than students themselves are the primary reasons for attrition (Billingsley, 2004; Westling et al, 2006). For example, Hastings and Brown (2002) found that a teacher variable, the use of maladaptive coping strategies, moderates the impact of students’ challenging behaviors on teacher burnout.…”
mentioning
confidence: 99%